2020
DOI: 10.1136/wjps-2019-000084
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in children undergoing surgery: incidence, risk factors and related adverse events

Abstract: BackgroundAlthough less common in adults, venous thromboembolism (VTE) in children is a highly morbid, preventable adverse event. While VTE has been well studied among pediatric hospitalized and trauma patients, limited work has been done to examine postoperative VTE in children undergoing surgery.MethodsUsing data from National Surgical Quality Improvement Project Pediatric database (NSQIP-P) from 2012 to 2016, a retrospective cohort analysis was performed to determine the incidence of, and risk factors for, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…There is a lack of previous studies of pediatric surgery‐associated VTE specifically evaluating ICU admission as a risk factor. However, previous studies did evaluate clinical acuity and markers of illness severity in other ways including ASA score, preoperative blood transfusions, preoperative ventilation, intubation, septic shock, and sepsis and found an association with increased risk of VTE 11,12,28‐30 . Ahn et al 12 and Sherrod et al 29 both found preoperative ventilator requirement was associated with the development of a VTE.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a lack of previous studies of pediatric surgery‐associated VTE specifically evaluating ICU admission as a risk factor. However, previous studies did evaluate clinical acuity and markers of illness severity in other ways including ASA score, preoperative blood transfusions, preoperative ventilation, intubation, septic shock, and sepsis and found an association with increased risk of VTE 11,12,28‐30 . Ahn et al 12 and Sherrod et al 29 both found preoperative ventilator requirement was associated with the development of a VTE.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies did evaluate clinical acuity and markers of illness severity in other ways including ASA score, preoperative blood transfusions, preoperative ventilation, intubation, septic shock, and sepsis and found an association with increased risk of VTE. 11 , 12 , 28 , 29 , 30 Ahn et al 12 and Sherrod et al 29 both found preoperative ventilator requirement was associated with the development of a VTE. Also Cairo et al 28 in 2018 and Sherrod et al 29 showed preoperative sepsis to be associated with the development of a postoperative VTE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations